OPTIMASI KONDISI PROSES PENGAMBILAN ASAM ALGINAT DARI ALGA COKLAT - Purwanti, Ani (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Seaweed is a marine product that has been widely used as a food ingredient. In addition, seaweed can also produces carrageenan and alginate which is an important compound in the industry. It is important to know the influential factors and the optimum process conditions to get the maximum alginate yield. In this study, it is to be obtained the optimum process conditions of taking alginate from brown algae (Sargassum cymosum). The seaweed powder was analyzed the water content and the ash content. To get alginate, this material is soaking in acid and to be extracted. It is continued with the process of gel formation and the process of conversion of alginic acid to sodium alginate to obtain dry Na-alginate. The variabel of the experiments are variation of the concen-tration and immersion time in hydrochloric acid solution, the variation of temperature, time, and concentration of sodium carbonate solution that used in the extraction process, the influence of the degree of acidity of the deposition process of alginic acid into alginic acid gel. The optimum conditions that obtained are the immersion time in 0.5M of hydro-chloric acid is 90 minutes, the extraction process conditions are 400C for 90 minutes with the sodium carbonate concentration 0.5 M. The solution acidity of the deposition rate is 3.